Children Rehabilitation Center the psychosocial rehabilitation of children and the youth in residential care through expressive arts theraphy - Acuesta, Patrisha A. (College of Architecture, University of the Philippines Diliman, 2019)
Child abuse is highly prevalent in the society, but the reporting is low due to stigma, cultural norms, fear, and other factors. Some victims of abuse are placed in a residential care center upon the recommendation of a social worker. However, the current conditions of this type of facility is the lack of resources. As a result, basic sustenance is the main priority, while resolving traumas is lesser in priority. Unresolved trauma and institutionalization of residential care centers pose negative long-term effects on the well-being of children, in their physical and mental health and behavior. To address this, the redesigning of residential care centers into rehabilitation centers will emphasize the need to address the psychological needs of children in treating their childhood traumas to allow their maximum development and contribute positively to the economic development. The proposed facility is situated in Tanay, Rizal in which its topography offers opportunities in creating safe and comfortable environment needed in rehabilitation among many others factors.